Bounded elastic potentials for rubberlike materials with strain‐stiffening effects. Issue 11 (25th August 2014) - Jin, Tianfu; Yu, Lidan; Yin, Zhengnan; Xiao, Heng
Abstract : Well‐known models for rubberlike elasticity with strain‐stiffening effects provide good predictions for unlimitedly, rapidly growing stress in a process of approaching a very large strain limit. According to such models, however, unbounded elastic strain energy would be generated as the strain limit is approached. To resolve this issue, a new, explicit approach is proposed to obtain multi‐axial elastic potentials based on uniaxial data and shear data. Then, a strain‐stiffening elastic potential is given to always yield bounded strain energy. Good agreement is achieved with a number of test data. Abstract : Well‐known models for rubberlike elasticity with strain‐stiffening effects provide good predictions for unlimitedly, rapidly growing stress in a process of approaching a very large strain limit. According to such models, however, unbounded elastic strain energy would be generated as the strain limit is approached. To resolve this issue, a new, explicit approach is proposed to obtain multi‐axial elastic potentials based on uniaxial data and shear data. Then, a strain‐stiffening elastic potential is given to always yield bounded strain energy. Good agreement is achieved with a number of test data.